ANALISIS KINERJA KEUANGAN DAERAH DALAM MENDUKUNG PELAKSANAAN OTONOMI DAERAH PEMERINTAH KOTA BUKITTINGGI (Studi Di Kota Bukittinggi Tahun Anggaran 2009-2013) - Dewi, Syukria; Agusti, Restu; Idrus, Rahmiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to analyze the financial performance of Bukittinggi government in supporting the implementation of regional autonomy. This study used a descriptive study with a qualitative approach. The results showed the level of independence of the City of Dublin is very low and does not yet support the implementation of regional autonomy with an average ratio of 10.44. The effectiveness of its budget on average 96.35 which is classified as not effective. Budget efficiency level of Bukittinggi was on average 0.66 were considered to be very efficient. The level of dependence of Bukittinggi is high with an average ratio of 89.42. Local revenue growth of Bukittinggi was on average 11.19 belonging increases and tends positive. Overall bukittinggi City local government is not independent and does not yet support the implementation of regional autonomy because it still has the instructive relationship pattern is a pattern of relations in which the role of the central government is more dominant than the role of the state itself.Keywords: decentralization, local independence,and regional growth